SERICIN AS A CHOLINERGIC MODULATOR IN ALZEIMER'S DISEASE INDUCED RAT - Peera, Kutagolla; Yellamma, Kuna (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: Alzheimer's disease (AD), characterized by formation of Amyloid plaques, neurofibrillary tangles and loss of neurons in the cerebral cortex and certain sub-cortical regions eventually results in gross atrophy of the affected regions, including degeneration in cholinergic regions. According to Cholinergic hypothesis, AD is caused by reduced synthesis of the neurotransmitter ACh, wherein the AChE levels were increased which causes damage to the cholinergic neurons finally leading to cognitive impairments. Today most of the drugs available in the market are Cholinesterase inhibitors to treat AD, these drugs temporarily de accelerate the progressive cognitive decline in some AD cases but not all other forms of dementia. Research on Alzheimer's proven the importance of the Antioxidants and AChEI to treat AD. To cure AD effectively it is necessary to identify a natural product with Antioxidant and AChEI activity. The Silk Protein, Sericin a natural protein has wide applications in the Pharma industry. Methods: The present study was aimed to evaluate potential AChE inhibitorâ€ activity of Sericin in AD-induced rat model by conducting experiments mainly on the Cholinergic system and also on the Morphometric and Cognitive aspects in control and experimental rats.\ Results: The results of the present study demonstrated that Sericin could effectively counteract the AChE activity in AD-induced rat and retains the ACh levels in the brain cholinergic regions. In the end of the experiment AD-induced rat showed recovery tendency in Morphometric and Cognitive aspects are the passive evidence for decline AD-induced AChE levels. Conclusion: From this study, it may suggest that Sericin act as a potential Cholinesterase inhibitor in AD. Â  Â 